Diversidade genética e filogeografia de Puma Yagouaroundi (Mammalia, Carnivora, Felidae) - Pires, Carla Bettin (2012)
Even though the Neotropical region has a vast biodiversity, it is also one of the least studied regions in the world, and harbors many species that still remain poorly known. An example is the wild cat jaguarundi (Puma yagouaroundi), which is up to now one the least known Neotropical felids. Of the few studies including this species, most address ecological aspects, and therefore little is known regarding its genetic diversity, evolutionary history and population structure. We have investigated these evolutionary aspects and inferred phylogeographic patterns of the jaguarundi by analyzing 1191 bp of the mitochondrial DNA and eight microsatellite loci. The results from both markers supported the recognition of at least two major phylogeographic groups (Northern and Southern), which do not corroborate the eight subspecies classically recognized for the jaguarundi. Physical barriers such as the Amazon river appear to have influenced the genetic differentiation between these two groups by restricting the gene flow between these broad geographic areas, in a pattern reminiscent of that observed in other felids. The results presented here contribute to increase the knowledge about the evolutionary history of this felid, and may be useful in the development of management strategies fostering its conservation in the wild.